Indirect treatment comparison of the efficacy of patisiran and inotersen for hereditary transthyretin-mediated amyloidosis with polyneuropathy. (2nd January 2021) - Gorevic, Peter; Franklin, Jaclyn; Chen, Jihong; Sajeev, Gautam; Wang, Jessie C. H.; Lin, Hollis
ABSTRACT: Introduction: Patisiran and inotersen are two therapies approved for the treatment of hereditary transthyretin-mediated (hATTR) amyloidosis with polyneuropathy, a rapidly progressive disease with a substantial clinical burden. This analysis indirectly compares the efficacy of patisiran and inotersen on neuropathy and quality of life (QOL). Methods: Published results from the NEURO-TTR study of inotersen and individual patient data from the APOLLO study of patisiran were used. Indirect comparisons were conducted for 15-month changes in neuropathy and QOL endpoints: modified Neuropathy Impairment Score +7 (mNIS+7Ionis, ), Norfolk Quality of Life-Diabetic Neuropathy (Norfolk QOL-DN) questionnaire, body mass index (BMI), and Polyneuropathy Disability (PND) score. Analyses were conducted under different assumptions about the impact of missing data and to adjust for baseline differences between studies. Results: Patisiran showed significantly greater treatment effects than inotersen for mNIS+7Ionis (mean difference: −12.3 [95% confidence interval: −21.4, −3.3]), Norfolk QOL-DN (−11.3 [−19.8, −2.9]), and BMI (1.0 [0.4, 1.7]). The proportion of patients with improvement or no change from baseline on PND score was higher for patisiran-treated patients (odds ratio: 8.9 [4.6, 17.5]). Results were consistent and robust across analyses and methods. Conclusions: Patisiran demonstrated greater treatment effects on neuropathy and QOL than inotersen in patients with hATTR amyloidosis with polyneuropathy.